55.2: A Novel Sn Paste Free Approach for Manufacturing Mini‐LED Display. (24th February 2021) - Yin, Yongming; Gao, Lu; Fan, Jack; Zhang, Lijun; Liu, Minggang; Sun, Yang; Chen, Shu-jhih; Zhang, Xin; Meng, Hong
Abstract : Mini/Micro LED are recognized as the fourth generation display technology due their superior performance. Backlights based on active‐matrix Mini‐LED (AM‐MLED) have been adopted in LCD modules and would soon be put into mass production. In this paper, a novel Sn paste free method was developed to manufacture Mini‐LED displays. This method is more simple and could successfully solve the short problem which is common for conventional approach. We believe this result would further extend the application of Mini‐LED in direct display area.